Effect of contrast water therapy duration on recovery of cycling performance: a dose-response study - Versey, N.; Halson, S.; Dawson, B. (European Journal of Applied Physiology, 2011)
This study investigated whether contrast water therapy (CWT) has a dose-response effect on recovery from high-intensity cycling. Eleven trained male cyclists completed four trials, each commencing with a 75-min cycling protocol containing six sets of five 15-s sprints and three 5-min time-trials in thermoneutral conditions. Ten minutes post-exercise, participants performed one of four recovery protocols: CWT for 6 min (CWT6), 12 min (CWT12), or 18 min (CWT18) duration, or a seated rest control trial. The CWT commenced in hot water (38.4 +/- 0.6°C) and alternated between hot and cold water (14.6 +/- 0.3°C) every minute with a 5-s changeover. The cycling protocol was repeated 2 h after completion of exercise bout one. Prior to exercise bout two, core temperature was lower in CWT12 (¡0.19 +/- 0.14°C, mean +/- 90% CL) and CWT18 (¡0.21 +/- 0.10°C) than control. Compared with control, CWT6 substantially improved time-trial (1.5 +/- 2.1%) and sprint performance (3.0 +/- 3.1%), and CWT12 substantially improved sprint total work (4.3 +/- 3.4%) and peak power (2.7 +/- 3.8%) in exercise bout two. All CWT conditions generally improved thermal sensation, whole body fatigue and muscle soreness compared with control, but no differences existed between conditions in heart rate or rating of perceived exertion. In conclusion, CWT duration did not have a dose-response effect on recovery from high-intensity cycling; however, CWT for up to 12 min assisted recovery of cycling performance.